The Effects of Language and Culture Variables to the Rehabilitation of Bilingual and Bicultural Consumers: A Review of Literature Study Focusing on Hispanic Americans and Asian Americans - Wong-Hernandez, Lucy; Wong, Daniel (Disability Studies Quarterly, 2002)
There has been a sizable growth in the proportion of multicultural populations in the United States from 1980- 1999, and an even larger proportion of culturally different populations is projected for the year 2009. Persons with disabilities, in particular, from Hispanic and Asian cultures represent a substantial proportion of the disabled population in the United States. Recent legislation mandates practices relevant to the rehabilitation, independent living, and employment needs of persons with disabilities in multicultural communities. Cultural variables affecting these populations, such as values and believes, rehabilitation expectations, and attitudes towards disabilities, are examined in this article. Language, acculturation and assimilation are also viewed as important contributors during the rehabilitation process of bicultural clients. The need for rehabilitation professionals to become more competent regarding multicultural issues, as mandated by new regulations, is emphasized.